The Role of Risk Perception and Accounting Information in Moderating Effect of Financial Literacy on Investment Decisions Based on Islamic Values (an Evidence in Indonesia and Malaysia) - Rendy Mirwan Aspirandi; Maheni Ika Sari (IECON: International Economics and Business Conference, 2025)
In 2024 National Financial Literacy and Inclusion findings showed that Indonesia citizens' financial literacy index was at 65.43 %. Indonesia's financial literacy index has significantly improved from 49.68% in 2022. For novice investors, company information is very useful for decision-making. Signaling theory, which incorporates the concept of asymmetric information into models of decision-making. This research focus on the moderating efect of Risk Perception and Accounting Information to Financial Literacy on Investment Decision. The final analysis comprised 45 usable questionnaires from respondents across Indonesia. The results of testing the research hypothesis show that Risk Perception and Accounting Information moderate the effect of Financial Literacy on Investment Decision. The investors who have a rational understanding will limit the amount of funds to invest in several investment instruments that have high risk. Investors who have high financial literacy will be strengthened by the risk perception and accounting information of an investment instrument will influence their investment decision making.